2021
DOI: 10.1007/s11469-021-00541-y
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Mediating Effects of Stress on Fear of COVID-19 and Well-being Using Structural Equation Modeling

Abstract: This study focuses on the effects of fear factor due to COVID-19 on stress and well-being of college students in India. The authors conducted a cross-sectional survey among 625 Indian students across various Indian universities and structural equation modeling (SEM) has been performed for analyzing the data. The findings of the study show a positive effect of fear of COVID-19 on stress with β = .27, p < 0.05, and a negative effect on well-being (β = −.13, p < 0.05). The results also depicted the mediating role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 50 publications
3
22
0
Order By: Relevance
“…Therefore, future studies using longitudinal designs are warranted to provide additional evidence in more rigorously exploring the causal relationships between fear of COVID-19 and other mental health-related factors. Third, although the present systematic review and meta-analysis analysed 91 studies, only three of them 46,118,126 assessed the associations between fear of COVID-19 and mental well-being. Therefore, further studies are needed to corroborate the evidence regarding the association between fear of COVID-19 and mental well-being.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, future studies using longitudinal designs are warranted to provide additional evidence in more rigorously exploring the causal relationships between fear of COVID-19 and other mental health-related factors. Third, although the present systematic review and meta-analysis analysed 91 studies, only three of them 46,118,126 assessed the associations between fear of COVID-19 and mental well-being. Therefore, further studies are needed to corroborate the evidence regarding the association between fear of COVID-19 and mental well-being.…”
Section: Discussionmentioning
confidence: 98%
“…For example, according to Servidio et al (2021) relationship between fear of COVID-19 and depression and anxiety was .17 and .28, respectively and whereas other research revealed the relationship between fear of COVID-19 and depression was .56 and anxiety was .71 (Alyami et al, 2020; Tsipropoulou et al, 2020). Also, Lathabhavan and Vispute (2021) found a moderate relationship between fear of COVID-19 and stress. Yet, some researchers found a relationship between fear of COVID-19 and stress was strong (Bakioğlu et al., 2020; Midorikawa et al., 2021).…”
Section: Fear Of Covid-19 and Mental Healthmentioning
confidence: 88%
“…In accordance with our results, previous studies have demonstrated that peripartum women experiencing fear of contracting COVID-19 or that a loved one would become infected was associated with higher stress ( Kumari et al, 2021 ; Puertas-Gonzalez et al, 2021 ). Currently, the construct "fear of COVID-19" has been introduced in the study of mental health, being related to various psychological outcomes such as stress and negative well-being ( Lathabhavan & Vispute, 2021 ). Furthermore, we found that negative change in mood and happiness were associated with increased stress.…”
Section: Discussionmentioning
confidence: 99%